Pelatihan Penyusunan Asesmen Brain Cyber untuk Mengidentifikasi Tingkat Kemampuan Berpikir Siswa di MTs Al Ihsan Banjaragung Bareng Jombang dengan Pendekatan Linguistik Sistemik Fungsional : Pengabdian - Chalimah, Chalimah; Utomo, Edy Setiyo; Khoirul Anshori (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This training aimed to identify the level of students' thinking ability related to brain cyber so that students could know the positive and negative aspects of the use of artificial intelligence. The training was attended by 42 students. Brain decay as a result of excessive use of brain cyber had several negative impacts, namely: (1) affecting language and behavioral development, (2) having academic impacts, (3) providing access to illegal content, violence, and dangerous sex, (4) leading to aggressive behavior. The results of the community service showed several improvements in students' thinking abilities as assessed from student understanding, namely: (1) 19% of students really understood, 79% of students understood, and 2% of students had less understanding about brain cyber and brain rot; (2) 21% of students really understood, 69% of students understood, and 10% of students had less understanding about the impact of brain cyber and brain rot; (3) 62% of students stated that this training was very useful and 38% of students stated that this training was useful; (4) 43% of students stated that this training was very appropriate and 57% of students stated that this training was in accordance with real conditions